Modelling Cost-Effectiveness of Biologic Treatments Based on Disease Activity Scores for the Management of Rheumatoid Arthritis in Spain - Ariel Beresniak; Rafael Ariza-Ariza; Jose Francisco Garcia-Llorente; Antonio Ramirez-Arellano; Danielle Dupont (Hindawi Limited, 2011)
Background. The objective of this simulation model was to assess the cost-effectiveness of different biological treatment strategies based on levels of disease activity in Spain, in patients with moderate to severe active RA and an insufficient response to at least one anti-TNF agent. Methods. Clinically meaningful effectiveness criteria were defined using DAS28 scores: remission and Low Disease Activity State (LDAS) thresholds. Monte-Carlo simulations were conducted to assess cost-effectiveness over 2 years of four biological sequential strategies composed of anti-TNF agents (adalimumab, infliximab), abatacept or rituximab, in patients with moderate to severe active RA and an insufficient response to etanercept as first biological agent. Results. The sequential strategy including etanercept, abatacept and adalimumab appeared more efficacious over 2 years (102 days in LDAS) compared to the same sequence including rituximab as second biological option (82 days in LDAS). Cost-effectiveness ratios showed lower costs per day in LDAS with abatacept (427 €) compared to rituximab as second biological option (508 €). All comparisons were confirmed when using remission criteria. Conclusion. Model results suggest that in patients with an insufficient response to anti-TNF agents, the biological sequences including abatacept appear more efficacious and cost-effective than similar sequences including rituximab or cycled anti-TNF agents.